Increasing the Magnetic Blocking Temperature of Single‐Molecule Magnets - Vieru, Veacheslav; Gómez‐Coca, Silvia; Ruiz, Eliseo; Chibotaru, Liviu F. (Angewandte Chemie International Edition, 2024)
The synthesis of single‐molecule magnets (SMMs), magnetic complexes capable of retaining magnetization blocking for a long time at elevated temperatures, has been a major concern for magnetochemists over the last three decades. In this review, we describe basic SMMs and the different approaches that allow high magnetization‐blocking temperatures to be reached. We focus on the basic factors affecting magnetization blocking, magnetic axiality and the height of the blocking barrier, which can be used to group different families of complexes in terms of their SMM efficiency. Finally, we discuss several practical routes for the design of mono‐ and polynuclear complexes that could be applied in memory devices. Despite three decades of intensive investigation of single‐molecule magnets (SMMs) there are still unexplored roads towards increasing their magnetization blocking temperature. In this Review, after short overview of key SMM compounds, the basic strategies for further enhancement of SMM performance for mononuclear and polynuclear complexes are presented.